2020
DOI: 10.1097/ijg.0000000000001492
|View full text |Cite
|
Sign up to set email alerts
|

Foveal Avascular Zone Measurement Via Optical Coherence Tomography Angiography and its Relationship With the Visual Field in Eyes With Open-angle Glaucoma

Abstract: Precis: The foveal avascular zone (FAZ) in optical coherence tomography angiography is significantly correlated with retinal inner layer thickness, Humphrey field analyzer (HFA) 10-2 sensitivity threshold, and mean deviation (MD) value in open-angle glaucoma patients. Purpose: The purpose of this study was to measure the FAZ area using optical coherence tomography angiography and investigate its relationship with retinal inner layer thickness and visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…e knowledge of the relationship of glaucoma with some vasospasm phenomena [32,33], such as migraines [34,35], syndrome of Raynaud, and peripheral vascular dysregulation [36], and also with sleep apnea [37,38], supports the idea of the participation of vascular dysfunction in the pathogenesis of glaucoma. However, despite the recent evolution in studies that assess blood flow in the ONH and especially vascular density through OCT-A, the high cost of this technology represents a limitation of its widespread use [12,[39][40][41][42][43][44]. Within this context, as previously described, the Laguna ONhE program represents a feasible lower cost option, analyzing conventional color retinography, to evaluate the vascular component by estimating Hb levels at the ONH.…”
Section: Discussionmentioning
confidence: 99%
“…e knowledge of the relationship of glaucoma with some vasospasm phenomena [32,33], such as migraines [34,35], syndrome of Raynaud, and peripheral vascular dysregulation [36], and also with sleep apnea [37,38], supports the idea of the participation of vascular dysfunction in the pathogenesis of glaucoma. However, despite the recent evolution in studies that assess blood flow in the ONH and especially vascular density through OCT-A, the high cost of this technology represents a limitation of its widespread use [12,[39][40][41][42][43][44]. Within this context, as previously described, the Laguna ONhE program represents a feasible lower cost option, analyzing conventional color retinography, to evaluate the vascular component by estimating Hb levels at the ONH.…”
Section: Discussionmentioning
confidence: 99%
“…• Foveal avascular zone is an area around the macula that is absent of blood vessel. Previous study found an increase in the area of the foveal avascular zone in glaucoma patients [22]. This finding was correlated with visual field abnormalities.…”
Section: Introductionmentioning
confidence: 51%
“…[43] applied modified VGG16 to the peripapillary OCTA images and found the areas under precision-recall curves of 0.97. In this study, we used wider field of OCTA image that included retinal and capillary vessels outside the peripapillary area because the correlation between foveal avascular zone and glaucoma was reported in [22]- [24]. In addition, because the prevalence of poor image quality was high [47]- [49], wider field of view that includes more clinical important area may provide more data for CNN to learn and predict in less severe case of poor quality image.…”
Section: Discussionmentioning
confidence: 99%
“…The association between the FAZ area and structural and functional damage has been assessed in previous studies. In a study by Igarashi et al, the FAZ area was significantly correlated with the RNFL thickness, GCC thickness, foveal threshold and MD value [ 32 ]. Li et al showed that an enlarged FAZ area was associated with a higher risk of RNFL thinning in OAG [ 33 ].…”
Section: Discussionmentioning
confidence: 99%